2020
DOI: 10.1016/j.heliyon.2020.e05569
|View full text |Cite
|
Sign up to set email alerts
|

Sources of perceived social support on resilience amongst parents raising children with special needs in Ghana

Abstract: Background: While parenting a child with special needs is burdensome, some parents do overcome through protective resources. Social support has been widely linked to this unique ability to overcome the challenges of raising a child with special needs. In spite of this, there is still paucity of research about the influence of the sources of perceived social support on this ability, known as resilience. Aim: This study examined three sources of perceived social support-family, friends and significant other-on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…The total score is obtained by summing the scores of all items and ranged from 12 to 84 with the higher scores denoting higher levels of perceived social support. The scale has demonstrated satisfactory reliability and validity and been successfully used in adolescents ( 32 , 33 ). In the present study, the Cronbach's alpha was 0.921, 0.857, 0.841, and 0.815 for total scale, family subscale, friend subscale and significant other subscale.…”
Section: Methodsmentioning
confidence: 99%
“…The total score is obtained by summing the scores of all items and ranged from 12 to 84 with the higher scores denoting higher levels of perceived social support. The scale has demonstrated satisfactory reliability and validity and been successfully used in adolescents ( 32 , 33 ). In the present study, the Cronbach's alpha was 0.921, 0.857, 0.841, and 0.815 for total scale, family subscale, friend subscale and significant other subscale.…”
Section: Methodsmentioning
confidence: 99%
“…This is because in this study, the ndings showed that family members, friends with other members of society stigmatised against persons living with colostomy. However, an important source of social support to individuals within Ghana are family members and friends [57,58]. Hence, being socially stigmatised by these group of persons could have signi cant implications for the wellbeing and self-esteem of Colostomates.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, being socially stigmatised by these group of persons could have signi cant implications for the wellbeing and self-esteem of Colostomates. Moreover, isolation and withdrawal from families and society due to one's colostomy condition can be a source of risk and affect the resilience of persons with colostomy since the availability of social support or lack of it has implications for resilience [57]. These ndings, thus, have implications for health professionals, especially, public health workers to create public awareness on colostomy and stoma conditions and encourage family members, as well as signi cant others of persons living with colostomy to provide support.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the perception and actuality that one is cared for, assisted by other people, and has a supportive social network can facilitate resilience and positive adaptability. Notably, the buffering role of family support against maladaptive coping has been well emphasized in the literature (Alsubaie et al, 2019; Dey & Amponsah, 2020; Munikanan et al, 2017). However, there is a paucity of research on the role of family support of parents of children living with disabilities and IDD in the African setting (Mckenzie & Ohajunwa, 2017; Oti‐Boadi et al, 2020; Sango, 2017).…”
Section: Family Support and Fqolmentioning
confidence: 99%
“…However, there is a paucity of research on the role of family support of parents of children living with disabilities and IDD in the African setting (Mckenzie & Ohajunwa, 2017; Oti‐Boadi et al, 2020; Sango, 2017). African culture is based on the collective perceptive that places higher value on the family as a unit of mutual concern (Dey & Amponsah, 2020). Thus, looking at the holistic view of the impact of family support received by parents of children with IDD in Nigeria may help understand its role in maintaining FQOL (Iacob et al, 2020).…”
Section: Family Support and Fqolmentioning
confidence: 99%